211 Co-production and implementation fidelity evaluation of the 'stay-one-step-ahead' child home safety programme. (20th November 2022) - Orton, Elizabeth; Stewart, Sabrina; Watson, Michael; Hayes, Mike; Patel, Tina; Timblin, Clare; Clarke, Rachael; Taylor, Michael; Coupland, Carol; Kendrick, Denise
Abstract : Background: Provision of home safety education and equipment prevents home injuries in children under 5 in socio-economically disadvantaged communities. We co-produced a low-cost home safety intervention (Stay-One-Step-Ahead, 'SOSA') with parents and health and early years family practitioners in a UK city, trained 142 practitioners in its use, and evaluated implementation fidelity over 2 years. SOSA comprised a home safety checklist used in routine child health reviews, monthly safety messages, safety activities and safety weeks. Methods: Implementation fidelity was assessed by triangulating data from parent and practitioner questionnaires, interviews and observations of parent/practitioner interactions. Quantitative data were analysed using logistic regression and thematic analysis was used for qualitative data. Results: Overall, 361 intervention and 401 control parents participated in the evaluation. Significantly more intervention parents reported receiving home safety advice (Odds Ratio (OR) 2.59 (95% CI 1.59–4.21), advice from ≥2 practitioners (OR 5.09; 1.34–19.33) and home safety leaflets (OR 1.90; 1.11–3.23). More intervention practitioners reported signposting parents to safety agencies (Intervention: 92%; Control: 20%). Whilst 4, 859 home safety checklists were completed (86% of reviews), they were often not used as intended. Safety weeks tended to be shorter than planned. Monthly safety message use varied by type of practitioner from 38%-75%. Home safety activities were undertaken in all 22 observed contacts. Conclusions: The SOSA intervention increased home safety advice received by parents but aspects of the intervention were often modified. Learning outcomes: Monitoring intervention fidelity is important when interpreting programme effectiveness results. Strategies to increase fidelity should be integral to intervention design.